Basic UV visible spectroscopy [filem jalur] (Fairfield, Conn. : Communication Skills Corp., 1972)
Contents : 1. Introduction to the theory of uv and visible spectra -- 2. Introduction to spectrop-hotometric measurements -- 3. Instrumentation part 1 : spectrophotometer components -- 4. Instrumentation part 2 : description and operating principles of typicalcommercial spectrophotometers -- 5. Applications part 1 : techniques of quantitative colorimetric analysis -- 6. Applications part 2